Pentingnya Mendeteksi Penyakit Jantung Bawaan Lebih Dini: Skrining Fase Prenatal dan Postnatal - Bayushi Eka Putra; Radityo Prakoso (Majalah Kedokteran Indonesia, 2022)
Congenital heart disease (CHD) may affect 1% of all pregnancies per year. This means, out of 100 babies there will be 1 baby who will experience CHD.1 Moreover, the latest data from the Global Burden of Disease Study 2017 shows the prevalence reaches 1.6%-1.7% for the Southeast Asia region, including Indonesia.2 On the other hand, Indonesia has a growth rate The population is 1.39% with 4.2-4.8 million babies born per year. 3 Thus, it can be estimated that the number of patients with CHD born in Indonesia is 71,400 to 81,600 babies per year.